OPTIMASI DESAIN PADA DINDING FURNACE DENGAN TEMPERATUR KERJA 1000 C - Khoirudin Khoirudin (JURNAL KAJIAN TEKNIK MESIN, 2018)
The aims of this research is to study and analysis on furnace walls with variation of hot face lining material types, variation of refractory material types, and variation of thickness of insulating materials to outer wall temperature at furnace with working temperature 1000 oC. This research uses a variety of hot face lining material in the form of ceramic fiber blanket with CR1260, CR1400, and CR1430, variations of refractory material in the form of refractory brick with the type NJM-20, NJM-23, and NJM-26, and using ROCKWOOL as an insulating material with a thickness variation of 50 mm, 75 mm, 100 mm. This research was simulated using Steady State Thermal ANSYS Mechanical (ANSYS Multiphysic) software. The result of the research shows the difference of the outer wall temperature value of the furnace. The highest wall temperature is in interaction with the wall without insulation, hot face lining material using CR1260, and NJM-26 as refractory material is 75.211 oC. While the lowest wall temperature is in the interaction of 100 mm thick insulation, hot face lining material using CR1430, NJM-20 as refractory material is  46.682 oC.